2012
DOI: 10.1371/journal.pone.0035600
|View full text |Cite|
|
Sign up to set email alerts
|

Adherence to Interferon β-1b Treatment in Patients with Multiple Sclerosis in Spain

Abstract: BackgroundAdherence to interferon β-1b (INFβ-1b) therapy is essential to maximize the beneficial effects of treatment in multiple sclerosis (MS). For that reason, the main objectives of this study are to assess adherence to INFβ-1b in patients suffering from MS in Spain, and to identify the factors responsible for adherence in routine clinical practice.Methodology/Principal FindingsThis was an observational, retrospective, cross-sectional study including 120 Spanish patients with MS under INFβ-1b treatment. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
3
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 31 publications
3
20
3
1
Order By: Relevance
“…This value was lower than the ones found in studies like a multicenter study conducted in Spain health care centers for MS patients using the Morisky & Green scale, which found an adherence rate of 68% (Fernandez et al, 2012).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…This value was lower than the ones found in studies like a multicenter study conducted in Spain health care centers for MS patients using the Morisky & Green scale, which found an adherence rate of 68% (Fernandez et al, 2012).…”
Section: Discussioncontrasting
confidence: 73%
“…It was observed that age (under 39 years old) was statistically significant, corroborating with Fernandez et al (2012). It is believed that the disease progression hinders adherence by older people.…”
Section: Discussionsupporting
confidence: 72%
“…Although a relevant proportion of patients discontinue IFNB due to lack of efficacy, an equally relevant proportion does this due to poor tolerability [6,7]. Furthermore, injection-related problems (anxiety, tiredness, injection-site pain or reactions) are other important reasons for non-adherence to IFNB, together with forgetting to administer, even in patients treated for more than 2 years [8,9,10]. A proportion ranging from 23 to 46% of patients treated with immunomodulating injective drugs have been reported as not adherent to IFNB treatment, in terms of both recommended dose and timing [7].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, a reduction of administration frequency of sc IFNB-1a or -1b can sometimes be intentionally (to reduce intolerable side effects) or unintentionally (in the case of forgetting to administer) adopted by patients [8,9,10]. However, the long-term consequences on disease activity of reducing administration frequency of sc IFNB are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there are no other published studies permitting comparison of this data, as most studies have assessed adherence in patients with MS with disease-modifying injection therapies 12 14 26. In a comparative study of fingolimod versus other parenteral therapies in patients with MS, adherence to oral fingolimod was 80–90%, a good approximation as patients’ characteristics might be similar 27.…”
Section: Discussionmentioning
confidence: 99%